Prevalence of atrial fibrillation and feasibility of pulmonary vein isolation after patent foramen ovale closure. (3rd October 2022) - Fabbricatore, D; Paolisso, P P; Gallinoro, E G; De Colle, C D C; Valeriano, C V; De Schouwer, K D S; Geelen, P G; Barbato, E B; De Potter, T D P
Abstract: Background: Data about prevalence and the risk of atrial fibrillation, stroke, and need for pulmonary vein isolation (PVI) after device closure of a patent foramen ovale (PFO) are still lacking. We aim to investigate the prevalence and the risk of atrial fibrillation after PFO closure and the feasibility of PVI in a PFO closure cohort compared to contemporary PVI without PFO closure. Methods: Retrospective observational study of consecutive patients undergoing PFO closure enrolled from February 2013 to September 2020. Patients were divided into 3 groups: i) patients without AF before and after the procedure (n=132), ii) patients with paroxysmal AF prior to the procedure (n=21), iii) patients with documented AF after the procedure (n=13). All patients with AF occurrence were treated with adequate anticoagulation therapy according to the current ESC Guidelines. We compared the procedural data of these patients to a matched contemporary cohort without previous PFO closure undergoing PVI in our center. AF and stroke prevalence and PVI feasibility after PFO closure were assessed at follow up. Results: One-hundred and sixty-six consecutive PFO closure patients were enrolled; the mean age was 54±13 years. Median follow-up was 3.5±2.5 years. During the study period, 21 patients had AF before or after the PFO closure (group 2) and 13 (7.8%) new onset AF (group 3). Stroke after the PFO closure occurred in 8 patients (4.8%), of which 4 in the group with new onset AF (30% of the group 3). Among the 34 patients with AF, 10 patients (6%) underwent a PVI. Compared to a contemporary matched PVI cohort, total procedural times and fluoroscopy times were significantly higher in the patients with previous PFO closure (108±15 vs 75±29, p=0.002 and 3±1.5 vs 8±7, p<0.001). Similar rate of AF relapses (p=0.198) was observed between the two groups, with a trend for higher rate of complication (pericardial effusion) for the cohort with previous PFO closure (p=0.06). Conclusion: This study shows that a more accurate screening and treatment of AF is needed in patients with cryptogenic stroke despite the presence of a PFO, possibly a bystander. In our study, 30% of patients with new onset AF after PFO closure, experienced a further stroke after the procedure. In case of AF, the indication for PVI should be considered prior to the PFO closure since it turns out to be more difficult in terms of procedural and fluoroscopy times and risks of complications after PFO closure. Funding Acknowledgement: Type of funding sources: Public Institution(s).